Analisis Struktur Penyajian dan Konten Nature of Science (NoS) pada Buku Teks Fisika SMA Pokok Bahasan Getaran Harmonis - Dhamayanti, Lina Fitri; Darma Putra, Ngurah Made; Handayani, Langlang (UPEJ Unnes Physics Education Journal, 2019)
Textbook is one of the teaching materials which have influence in the learning activities. The research aimed to know whether textbook of Physics of SMA class X that was used in Pati Regency that has used learning analogy, how the structure of presentation of the concept, has loaded NoS content, how presented the exercise questions. Content in A and B books based on the content of NoS was still dominated by one aspect of the theory and law aspects of 56.68% in books A and 71.87 in book B. The question problems in book A and B were dominated by the applied category of 51,19% and 41,94%. Content in books A and B based on analogy loads was still poorly presented. The concepts that were presented in the two books are different.